Electron-capture and Low-mass Iron-core-collapse Supernovae: New Neutrino-radiation-hydrodynamics Simulations - Radice, David; Burrows, Adam; Vartanyan, David; Skinner, M. Aaron; Dolence, Joshua C. (The Astrophysical journal, 2017)
We present new 1D (spherical) and 2D (axisymmetric) simulations of electron-capture (EC) and low-mass iron-core-collapse supernovae (SN). We consider six progenitor models: the ECSN progenitor from Nomoto; two ECSN-like low-mass low-metallicity iron-core progenitors from A. Heger (2016, private communication); and the 9, 10, and 11 (zero-age main-sequence) progenitors from Sukhbold et al. We confirm that the ECSN and ESCN-like progenitors explode easily even in 1D with explosion energies of up to a 0.15 Bethes ( ), and are a viable mechanism for the production of very-low-mass neutron stars. However, the 9, 10, and 11 progenitors do not explode in 1D and are not even necessarily easier to explode than higher-mass progenitor stars in 2D. We study the effect of perturbations and of changes to the microphysics and we find that relatively small changes can result in qualitatively different outcomes, even in 1D, for models sufficiently close to the explosion threshold. Finally, we revisit the impact of convection below the protoneutron star (PNS) surface. We analyze 1D and 2D evolutions of PNSs subject to the same boundary conditions. We find that the impact of PNS convection has been underestimated in previous studies and could result in an increase of the neutrino luminosity by up to factors of two.